Analysis of Basic Skills in the Futsal Game (Empirical Study of Futsal Extracurricular Participants at SMP Negeri 2 Tawangmangu) - Purnama, Mahendra Aji; Warthadi, Anugrah Nur; Nurhidayat (Fair Play, 2024)
The sport of futsal is a game played by two teams, each consisting of five players. The game emphasizes cooperation between players and combines elements of football and basketball. Futsal is popular among students, including at SMP Negeri 2 Tawangmangu, which provides extracurricular futsal as a forum for student talent development. Despite the high demand, the pandemic has hampered participation. With adequate facilities, but still lacking some facilities, students are expected to develop basic futsal skills such as passing, control, shooting, dribbling, and heading. This study aims to measure the level of basic futsal skills of SMP Negeri 2 Tawangmangu students. The results showed that students' basic futsal skills were in the good category, with 10 students declared good, 9 sufficient, 5 less, and 1 very less. The findings concluded that the level of futsal skills of extracurricular participants at the school was good.